Developing A Narrative Storybook Based on East Nusa Tenggara Folktales as A Learning Medium for Senior High School Students at Senior High School Reformasi Plus Noelbaki - Herlin Betty; Soleman Dapa Taka; Antonia Tefa (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to develop a storybook based on East Nusa Tenggara (NTT) folktales as a learning medium for Grade X students at SMAS Reformasi Plus Noelbaki and to examine students’ perceptions of the storybook. The study was conducted because students experienced difficulties in understanding narrative texts, particularly in vocabulary mastery and identifying generic structures, and required more engaging learning media. NTT folktales were chosen because they contain local cultural values that can make learning more meaningful and help students strengthen their cultural awareness. This study employed a Research and Development (R&D) approach using the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. Data were collected through questionnaires, interviews, classroom observation, and expert validation involving a material expert, a media expert, and a language expert. The findings showed that the developed storybook, which integrates five selected NTT folktales, illustrations, vocabulary lists, and exercises, was categorized as “very feasible” with an average validation score of 86.88%. The effectiveness of the storybook was measured through students’ classroom participation, learning engagement, and responses from questionnaires and interviews during the implementation stage. The results indicated that students became more active, motivated, and interested in learning narrative texts. In addition, students expressed highly positive perceptions toward the storybook because it helped them understand narrative texts more easily and increased their cultural awareness. Therefore, this study contributes to the development of culturally relevant English learning media by integrating local folktales into narrative text learning for senior high school students.